Hubungan Pola Makan Dan Status Gizi Dengan Kejadian Diabetes Melitus - Ruwiah; Suhadi; Deandra Viyanti Mansur (STIKES Columbia Asia Medan, 2025)
Diabetes mellitus is one of the health problems whose incidence is increasing and is often complained about by people around the world. Globally, Indonesia ranks fifth in the number of diabetes mellitus cases with 19.5 million people. Dietary patterns, including energy intake, carbohydrates, protein, fat, and nutritional status, play a role in the incidence of diabetes mellitus. The purpose of this study was to determine the relationship between dietary patterns and nutritional status with the incidence of diabetes mellitus at the Bahteramas Regional General Hospital in Southeast Sulawesi Province. The study design used a cross-sectional method with purposive sampling. The study respondents were inpatients aged ≥ 20 years. Data analysis used the chi-square test. The study was conducted in April-May 2025. The results of the analysis showed that there was a significant relationship between dietary patterns (p=0.008) and the incidence of diabetes mellitus. However, no significant relationship was found between nutritional status (p=0.421) and the incidence of diabetes mellitus. Thus, it is important to pay attention to nutrient consumption patterns and nutritional status in the prevention and management of diabetes mellitus.